- #1

- 7

- 0

AN + BL = 1

(1 - A)^(M-1) x = k

(1 - B)^(M-1) y = k

It s ok to solve it for the limit case as N, L, and M go to infinity.

- Thread starter kayhm
- Start date

- #1

- 7

- 0

AN + BL = 1

(1 - A)^(M-1) x = k

(1 - B)^(M-1) y = k

It s ok to solve it for the limit case as N, L, and M go to infinity.

- #2

- 22,089

- 3,286

- Last Post

- Replies
- 3

- Views
- 4K

- Last Post

- Replies
- 1

- Views
- 639

- Replies
- 5

- Views
- 594

- Last Post

- Replies
- 4

- Views
- 2K

- Replies
- 14

- Views
- 771

- Last Post

- Replies
- 5

- Views
- 1K

- Last Post

- Replies
- 2

- Views
- 700

- Last Post

- Replies
- 2

- Views
- 2K

- Last Post

- Replies
- 1

- Views
- 1K

- Last Post

- Replies
- 4

- Views
- 2K